Replacement of dietary saturated fat with unsaturated fats increases numbers of circulating endothelial progenitor cells and decreases numbers of microparticles: findings from the randomized, controlled Dietary Intervention and VAScular function (DIVAS) study. Issue 6 (8th May 2018) - Weech, Michelle; Altowaijri, Hana; Mayneris-Perxachs, Jordi; Vafeiadou, Katerina; Madden, Jacqueline; Todd, Susan; Jackson, Kim G; Lovegrove, Julie A; Yaqoob, Parveen
ABSTRACT: Background: Endothelial progenitor cells (EPCs) and microparticles are emerging as novel markers of cardiovascular disease (CVD) risk, which could potentially be modified by dietary fat. We have previously shown that replacing dietary saturated fatty acids (SFAs) with monounsaturated or n–6 (ω-6) polyunsaturated fatty acids (MUFAs or PUFAs, respectively) improved lipid biomarkers, blood pressure, and markers of endothelial activation, but their effects on circulating EPCs and microparticles are unclear. Objective: The Dietary Intervention and VAScular function (DIVAS) Study investigated the replacement of 9.5–9.6% of total energy (%TE) contributed by SFAs with MUFAs or n–6 PUFAs for 16 wk on EPC and microparticle numbers in United Kingdom adults with moderate CVD risk. Design: In this randomized, controlled, single-blind, parallel-group dietary intervention, men and women aged 21–60 y ( n = 190) with moderate CVD risk (≥50% above the population mean) consumed 1 of three 16-wk isoenergetic diets. Target compositions for total fat, SFAs, MUFAs, and n–6 PUFAs (%TE) were as follows: SFA-rich diet (36:17:11:4; n = 64), MUFA-rich diet (36:9:19:4; n = 62), and n–6 PUFA-rich diet (36:9:13:10; n = 66). Circulating EPC, endothelial microparticle (EMP), and platelet microparticle (PMP) numbers were analyzed by flow cytometry. Dietary intake, vascular function, and other cardiometabolic risk factors were determined at baseline. Results: Relative to the SFA-rich diet, MUFA- and n–6 PUFA-rich diets decreased EMP (−47.3%, −44.9%) respectively and PMP (−36.8%, −39.1%) numbers (overall diet effects, P < 0.01). The MUFA-rich diet increased EPC numbers (+28.4%; P = 0.023). Additional analyses that used stepwise regression models identified the augmentation index (measuring arterial stiffness determined by pulse-wave analysis) as an independent predictor of baseline EPC and microparticle numbers. Conclusions: Replacement of 9.5–9.6%TE dietary SFAs with MUFAs increased EPC numbers, and replacement with either MUFAs or n–6 PUFAs decreased microparticle numbers, suggesting beneficial effects on endothelial repair and maintenance. Further studies are warranted to determine the mechanisms underlying the favorable effects on EPC and microparticle numbers after SFA replacement. This trial was registered at www.clinicaltrials.gov as NCT01478958.